2009
DOI: 10.1007/s00268-009-0267-0
|View full text |Cite
|
Sign up to set email alerts
|

More Than 25 Years of Surgical Treatment of Hydatid Cysts in a Nonendemic Area Using the “Frozen Seal” Method

Abstract: Background Hydatid disease of the liver remains endemic in the world and is an imported disease in The Netherlands. The aim of this study was to evaluate the treatment and outcome of surgically treated patients for hydatid disease in a single center in The Netherlands. Methods This retrospective study included 112 consecutive patients surgically treated for hydatid disease between 1981 and 2007. The primary outcome was relapse of the disease. Secondary outcomes were infections, complications, reoperations, len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
(130 reference statements)
0
17
0
Order By: Relevance
“…In addition, a study in 2010 observed the recurrence of hydatid disease to be 8% during a median follow-up period of 33 months. Other studies indicated a reported incidence between 1.1%-25%, which may be caused by spilling of the cyst's contents during a previous operation [4]. In Iraq, in which 14.5% of patients had cystic lesions in the liver or other abdominal organs, no recurrences of hydatidosis were observed, except in 1 patient who was referred to a surgery department as a case of pleural effusion drainage despite albendazole therapy [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a study in 2010 observed the recurrence of hydatid disease to be 8% during a median follow-up period of 33 months. Other studies indicated a reported incidence between 1.1%-25%, which may be caused by spilling of the cyst's contents during a previous operation [4]. In Iraq, in which 14.5% of patients had cystic lesions in the liver or other abdominal organs, no recurrences of hydatidosis were observed, except in 1 patient who was referred to a surgery department as a case of pleural effusion drainage despite albendazole therapy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Other surgeons recommended albendazole for 3 21-day courses with 10-day rest periods between courses and only 1 recurrence was reported from month 1-72 [26]. Some suggested that the frozen-seal technique is safe and effective for the surgical treatment of hydatid disease in non-endemic areas and results showed the recurrence rates and mortality rates were lower [4]. In our study, surgical methods and the use of chemotherapeutic agents such as albendazole were employed, even though the secondary or recurrence rates were higher than in other studies (6.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Over the years, a few contributions from Western centres have appeared, originating mostly in Europe. 7,9,10 In contrast, the North American experience with hydatid disease remains extremely limited owing to the rarity of this pathology and is restricted to rare series and occasional case reports. 8,11 To our knowledge, the present series represents the largest combined surgical experience with hydatid disease of the liver in North America.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In contrast, liver surgeons working in Western centres -particularly North American hospitals -can be expected to treat only a handful of such patients over the course of their careers. [7][8][9][10][11] In this context, it becomes particularly important to define surgical treatment strategies that are specific to the expertise of Western liver surgeons, which is lacking in the literature. We sought to review a single North American tertiary care centre's experience with patients who underwent liver surgery for hydatid cysts of the liver.…”
mentioning
confidence: 99%